Default Risk, Yield Spreads, and Time to Maturity - Rodriguez, Ricardo J. (Journal of Financial and Quantitative Analysis, 1988)
This paper extends the default model of yield spreads for bonds by showing that, in general, they are a complex function of maturity and, in particular, are not always monotonically increasing, contrary to what one traditional view suggests. Our results may help explain the apparently conflicting empirical results found in the literature.